Pengaruh Penggunaan Media Peta Buta Terhadap Hasil Belajar Siswa pada Mata Pelajaran Ilmu Pengetahuan Sosial di Sekolah Menengah Pertama Negeri 46 Pekanbaru - Trisastia Wani; Sakilah Sakilah; Devi Arisanti; Alimuddin Alimuddin; Wardani Purnamasari (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study examined the effect of using Blind Map media on student learning outcomes in Social Science subjects at State 46 Pekanbaru Junior High School. Due to the low level of achievement and understanding of the material, this study used a quantitative experimental approach. Approximately 80 seventh grade students were purposively identified, with grades E and D as the experimental and control groups respectively. The results showed that there was a significant effect of the Blind Map media on learning outcomes, with t observation = 24.670 > t table = 0.304 and t observation = 24.670 > t table = 0.304, indicating the rejection of H₀. The effect size of 2.859 indicates a slow rate of change, suggesting that increased use of the Blind Map media can improve student learning outcomes.